Global monitoring report 2006 : Millennium development goals, strengthening mutual accountability, aid, trade & governance - World Bank (Washington, 2006)
This Third edition provides an integrated assessment of the policies and actions by developing countries, developed countries, and international financial institutions that are needed to achieve the Millennium Development Goals. The Report provides an assessment of how the various parties are playing their part under the agreed upon development partnership and highlights progress on the development policy agenda. This edition focuses in particular on aid effectiveness and governance reforms.
Keywords: Global monitoring report, 2006